Eksplorasi Pemahaman Akuntansi Pemerintahan dan Tingkat Pendidikan Aparatur Desa Pada Kualitas Laporan Keuangan Desa (Studi Kasus Pada Desa Langonsari Kec Pameungpeuk Kab Bandung) - Anita, Dian; Putri, Fita Rahmawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to explore the understanding of government accounting and analyze the influence of village officials' education level on the quality of village financial reports. The research was conducted in Langonsari Village, Pameungpeuk District, Bandung Regency, using a qualitative case study approach. Data collection was carried out through in-depth interviews, observations, and document analysis to obtain a comprehensive picture of the implementation of government accounting at the village level. The findings indicate that the understanding of government accounting among village officials varies depending on their educational background and work experience. Moreover, the education level plays a crucial role in determining the quality of village financial reports, particularly in terms of compliance with government accounting standards and reporting transparency. The results of this study provide insights for local governments to enhance the capacity of village officials through more intensive training and education, ensuring more accountable and transparent village financial management.